Strategi Pengembangan Objek Wisata Salib Kasih di Desa Simorangkir Julu Kecamatan Siatas Barita Kabupaten Tapanuli Utara - Nike Widia Purnama Telaumbanua; Tio R.J.Nadeak; Harisan Boni Firmando; Mery Silalahi; Jupalman Welly Simbolon (Lembaga Pengembangan Kinerja Dosen, 2024)
The Salib Kasih tourist attraction is one of the leading potential tourist attractions in North Tapanuli district which offers spiritual tourism as well as natural and cultural panoramas. The purpose of this research is to determine the Development Strategy for the Salib Kasih tourist attraction. Salib Kasih is a tourist attraction created to commemorate the services of Christian missionary from Germany Ingwer Ludwig Nommensen who began his mission in Batak Land and is where Ingwer Ludwig Nommensen looked towards Rura Silindung below. This research uses qualitative research methods, with data collection techniques through interviews, observation and documentation of several informants, namely the Tourism and Tourism Office and tourism business actors. Through the results of research conducted by the author, the development strategy for the Salib Kasih tourist attraction carried out by the Tourism Office is to improve facilities, add facilities, collaborate with other agencies and carry out promotions to increase the attractiveness of the Salib Kasih tourist attraction.